Scalar field couplings to quadratic curvature and decay into gravitons - Yohei Ema; Kyohei Mukaida; Kazunori Nakayama (Journal of High Energy Physics, 2022)
Abstract Any field, even if it lives in a completely hidden sector, interacts with the visible sector at least via the gravitational interaction. In this paper, we show that a scalar field in such a hidden sector generically couples to the quadratic curvature via dimension five operators, i.e., ϕR 2, ϕR μν R μν , ϕR μνρσ R μνρσ , ϕR μνρσ R ~ μνρσ $$ {\overset{\sim }{R}}^{μ ν ρ σ} $$ , because they can emerge if there exist particles heavier than it. We derive these scalar couplings to the quadratic curvature by integrating out heavy particles in a systematic manner. Such couplings are of phenomenological interest since some of them induce the scalar decay into the graviton pair. We point out that the decay of a scalar field can produce a substantial amount of the stochastic cosmic graviton background at high frequency since the suppression scale of these operators is given by the mass of heavy particles not by the Planck scale. The resultant graviton spectrum is computed in some concrete models.